Penerapan Metode Scramble untuk Meningkatkan Prestasi Belajar SKI Kelas V MI Al-Iman Sorogenen - Ani Muflihah; Khanif Maksum (LITERASI (Jurnal Ilmu Pendidikan), 2015)
Abstract This study aims to determine the planning scramble method is applied in teaching Islamic Cultural History (SKI), to determine the feasibility of the methods scramble on the subjects of Cultural History of Islam and this research is also expected to improve student achievement in grade V MI Al-Iman Sorogenen. This type of research is the Classroom Action Research (Classroom Action Research) conducted in MI Al-Iman Sorogenen. This study uses two cycles of learning with two meetings in the first cycle, and the first meetings on the second cycle. The method used to scramble method is applied with a group discussion on the cycle I and II. In the discussions, the students were divided into small groups resulting in effective information exchange among members. The results showed that the planning of the use of methods scramble on learning SKI class V MI Al-Iman Sorogenen running smoothly starting from the manufacture of Learning Implementation Plan (RPP), card making questions and answer cards, make sheets of pre-test and post-test, and make the observation sheet , Scramble method can also be implemented and applied in teaching Islamic Cultural History, with the effect size of 7.3. Improved student achievement shows the average value of pre test cycle I is 46.6% increase in post test becomes 53.33%. While in the second cycle showed an increase learning achievement of the average value of pre-test 53.33% increase in post-test to 80%. Thus, an increase learning achievement SKI class V MI Al-Iman Sorogenen based on the results of post test is 26.7%. Keyword: scramble method, achievement